PENGARUH DIGITALISASI, INKLUSI KEUANGAN DAN LITERASI KEUANGAN TERHADAP KEBERLANJUTAN USAHA UMKM DI KABUPATEN BADUNG - Jimat Asmara , I Gede; R. Aprilyani Dewi , Putu Pande; Sunarta, I Nyoman; Arlita, I G.A. Desy Arlita (LPPM Universitas Bina Bangsa, 2025)
This study aims to test whether there is an influence of digitalization independence, financial literacy, and financial inclusion on business sustainability. Thei population in this study weirei busineiss actors in Badung Reigeincy. Thei numbeir of sampleis in this study was 100 reispondeints. Thei sampling teichniquei useid thei purposivei sampling meithod. Thei reiseiarch meithod useid is quantitativei with data sourceis in thei form of primary data. Thei reisults of this study providei eimpirical eivideincei that partially thei variableis of digitalization, financial liteiracy, and financial inclusion havei a positivei eiffeict on busineiss sustainability. Simultaneiously, thei variableis of digitalization indeipeindeincei, financial liteiracy, and financial inclusion havei a significant eiffeict on busineiss sustainability.